PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI C SDN 004 TEMBILAHAN KOTA - Retno Ambarwati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low grade science students learning outcomes VI C SDN 004 Tembilahan Kota, Of the 23 students, only 9 students (39.13%) were completed. Based on this the researchers conducted the study by applying image media to improve learning outcomes IPA. This research is a class act who performed a total of two cycles consisting of two meetings, the study was conducted with four phases, namely planning, implementation stage, the stage of observation and reflection stages. The study states that science learning outcomes of students has increased in each cycle, this is evidenced by the increasing average student learning outcomes, the preliminary data the average student learning outcomes at 66.00 has increased in the first cycle of up to 83.30, and increased up to 91.74. Based on these results, it can be concluded that the application of drawing media can improve learning outcomes VI grade science students SDN 004 Tembilahan Kota.